Parental Judgments of Infant Pain: Importance of Perceived Cognitive Abilities, Behavioural Cues and Contextual Cues - Rebecca R Pillai Riddell; Melanie A Badali; Kenneth D Craig (Pain Research and Management)
BACKGROUND: Despite blatant indications, such as behavioural and contextual cues, infant pain is often undermanaged by adult caretakers. The belief that infants are limited in their abilities to comprehend the meaning of an experience or recall that experience has been used to minimize or deny the need for intervention in this vulnerable population.